Cyberbullying prevalence in Australian adolescents: Time trends 2015-2020. (3rd July 2022) - Trompeter, Nora; Jackson, Emma; Sheanoda, Veronica; Luo, Aileen; Allison, Kimberley; Bussey, Kay
ABSTRACT: Cyberbullying is a major issue during adolescence; however, little is known about trends in its prevalence, or how the early stages of the COVID-19 pandemic has impacted these trends. This study investigated how the prevalence of cyberbullying and associated factors (depression, social anxiety, and coping self-efficacy) have changed from 2015 to 2020. The study used self-report data from Australian high-school students ( n = 1418) aged 11–16 years, collected yearly from 2015 to 2020. Findings showed that while prevalence of cyber victimization increased over time, prevalence of cyber perpetration did not. However, sharp rises of both cyber victimization and cyber perpetration were noted during the early stages of the COVID-19 pandemic in 2020. While no increases in mental health difficulties were reported in 2020, increases in cyberbullying and decreases in coping self-efficacy are concerning.